THE LUTHER OF SHIâI ISLAM - al-Qurtuby, Sumanto (IAIN Walisongo Semarang, 2012)
Abstract Â This paper examines socio-historical roots of the emergence of the idea of âIslamic Protestantismâ within Iranian Shiâi tradition. The central focus of this study is to present thoughts and activities of so-called âIranian Luthersâ as the agents, actors, and prime movers of the birth of Islamic reformation in Iran. These actors whose ideas of Islamic reformation have had great influences and reached broader audiences beyond Iranian territory include Sayyid Jamal al-Din al-Afghani, Ali Shariâati, Mehdi Bazargan, Hashem Aghajari, and Abdul Karim Soroush. There are a number of Iranian reformers deserve credits for their thoughtful, controversial ideas of Islamic reformations. These Iranian reformers are considered âthe Luthers of Islamâ for their deep admiration of Martin Lutherâs Protestant Reformation, and their calls for Islamic reformation just like Luther did in the sixteenth century Europe. By the socio-historical and descriptive analysis, this paper is not intended to compare two religious reformations in Iran and Europe, but rather to study and analyze their notions with regard to Islamic reformation. Â *** Artikel ini membicarakan tentang akar sosio-historis munculnya gagasan âProtestanisme Islamâ dalam tradisi Syiâah Iran, dengan fokus kajian pemikiran dan gerakan yang disebut âLuther Iranâ sebagai agen, aktor, dan penggerak utama lahirnya reformasi Islam di Iran. Ide-ide reformasi Islam memiliki pengaruh besar dan mencapai khalayak yang lebih luas di luar wilayah Iran termasuk Sayyid Jamal al-Din al-Afghani, Ali Shariâati, Mehdi Bazargan, Hashem Aghajari, dan Abdul Karim Soroush. Sejumlah reformis Iran layak mendapatkan perhatian karena pemikiran, ide-ide kontroversial mereka dalam reformasi Islam. Para reformis Iran dianggap sebagai âLuther Islamâ karena kekaguman mendalam mereka terhadap Martin Luther, dan mereka menghendaki reformasi Islam seperti yang terjadi pada masa Luther di Eropa abad keenam belas. Dengan analisis sosio-historis dan deskriptif, tulisan ini tidak dimaksudkan untuk membandingkan dua reformasi keagamaan di Iran dan Eropa, melainkan untuk mempelajari dan menganalisis gagasan-gagasanmereka mengenai reformasi Islam. Â Keywords: Iranian Shiâi Tradition, Iranian Luthers, Islamic reformation, Islamic Protestantism